SELECTION OF DRUGS AND ITS PHARMACOLOGICAL EFFECTS IN THE TREATMENT OF HEART FAILURE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Heart failure - a syndrome caused by decompensated myocardial dysfunction, is manifested by an increase in the volume of cellular fluid and a decrease in the perfusion of organs and tissues. The main pharmacotherapeutic effect of cardiac glycosides occurs with an increase in systole, "positive inotropic effect". related to the direct effect of medicinal substances on the heart: deuritics are also used in a complex way to reduce the side effects of glycosides and improve their effect.